Appendix 5.6: Excerpts from Agapita Trajano; Archimedes Trajano, Plaintiffs-Appellees, v. Ferdinand E. Marcos, Defendant, and Imee Marcos-Manotoc, Defendant-Appellant - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
The facts of this case are no longer in dispute, as far as U.S. courts are concerned. Imelda “Imee” Marcos-Manotoc, through forces under her control, caused the wrongful death of student Archimedes Trajano in 1977. It should be noted that these facts became undisputed because of Imee Marcos’s default in 1986. In that year, the Marcoses successfully had the case dismissed on purely legal—i.e., jurisdictional—grounds. However, that same dismissal was reversed, specifically by Trajano v. Marcos , 878 F2d 1439, an unpublished disposition decided on 10 July 1989. Having opted not to challenge the facts stated by the plaintiffs, the defense strategy adopted by the Marcoses led to Imee’s undoing. She tried to have the entry of default lifted in 1991 on the basis of insufficiency of service, but that attempt failed; had they not been adequately served in 1986, would the Marcoses have been able to file their defense? Despite the case having been decided with finality in the United States, it was not successfully enforced in the Philippines.  Manotoc v. Court of Appeals , G.R. No. 130974, promulgated on 16 August 2006, written by Justice Presbitero Velasco, dismissed the civil case complaint that was meant to lead to the enforcement of the U.S. decision purely on technical grounds—i.e., once again, insufficiency of service.